Return to the Real, Part II: Cultural Feedback Loops in Psychoactive Drug Experiences - ten Berge, Jos (Journal of Anomalous Experience and Cognition, 2025)
Having identified a typically Modernist view of what (psychedelic) drugs “do” in “Return to the Real, Part I,” this follow-up article discusses some of the implications of this observation for drug studies in general and for the notion of set and setting in particular. A fourfold diagram is proposed in which the cultural set and setting, the individual set and setting, the drug experience, and its articulation back into culture, are seen as interconnected elements of a feedback loop. Different processes within this loop are described and illustrated with historical examples. Since the main effect of (psychedelic) drugs is to amplify, it follows that their use tends to reinforce prior beliefs. And since feedback loops are by definition cyclical and repetitive, their effect on a sociocultural level would have to be conservative too. On this level, transformative effects are rather due to impactful articulations of drug experiences in receptive environments. Finally, this paper suggests that drug studies require a minimal knowledge of cultural history.